The Feasibility of a Hypercontent Digital Magazine as Teaching Material on the Human Reproductive System - Alamsyah, Muhammad Radian Nur; Maulina, Rika; Ramadani, Shefa Dwijayanti (Universitas Tidar, 2025)
This research was motivated by problems identified in a school where the presentation of teaching materials on the human reproductive system did not align with the characteristics of Generation Z students, thereby reducing their interest in learning. To address this issue, relevant and engaging teaching materials are needed. Therefore, a digital magazine format was selected as a potential solution. This study aims to assess the feasibility of a hypercontent digital magazine as teaching material for the human reproductive system, based on material and media aspects. The research employed a Research and Development (R&D) design adapted from Borg and Gall (1983) which is limited to the stages of developing the initial product and conducting expert validation. The research results showed that the product achieved a feasibility rating of 80% (High) for the media aspect and 78% (high) for the material aspect. These findings suggest that the developed hypercontent digital magazine is feasible for use as teaching material on the human reproductive system.